Serotype 1 pneumococcus: epidemiology, genomics, and disease mechanisms. Issue 6 (June 2022) - Chaguza, Chrispin; Yang, Marie; Jacques, Laura C.; Bentley, Stephen D.; Kadioglu, Aras
Abstract : Streptococcus pneumoniae (the 'pneumococcus') is a significant cause of morbidity and mortality worldwide, causing life-threatening diseases such as pneumonia, bacteraemia, and meningitis, with an annual death burden of over one million. Discovered over a century ago, pneumococcal serotype 1 (S1) is a significant cause of these life-threatening diseases. Our understanding of the epidemiology and biology of pneumococcal S1 has significantly improved over the past two decades, informing the development of preventative and surveillance strategies. However, many questions remain unanswered. Here, we review the current state of knowledge of pneumococcal S1, with a special emphasis on clinical epidemiology, genomics, and disease mechanisms. Highlights: Pneumococcal serotype 1 (S1) is a major cause of invasive pneumococcal disease (IPD) globally, especially in Africa, South America, and Asia. Pneumococcal S1 strains are frequently found in the tissues and fluids of IPD patients while they are rarely isolated from the nasopharynx of asymptomatic carriers, including in high pneumococcal carriage and disease settings. A select number of S1 clones are frequently associated with outbreaks and epidemics, especially in closed communities and highly vulnerable groups. Whole-genome sequencing (WGS) has provided valuable insights on the clones, lineages, evolutionary dynamics, and phylogeographic structure of pneumococcal S1 globally.